Long-Term Effect of Acupuncture on the Medical Expenditure and Risk of Depression and Anxiety in Migraine Patients: A Retrospective Cohort Study - Liao, Chung-Chih; Liao, Ke-Ru; Lin, Cheng-Li; Li, Jung-Miao (Frontiers in Neurology, 2020)
Background: Migraine, a common neurological disorder, increases the risk of psychiatric disorders. Currently, the efficacy of conventional therapies is considered unsatisfactory. Acupuncture has been gaining popularity in treatment of neuropsychiatric disease. This study aimed to investigate the effect of acupuncture on medical expenditure and the risk of depression and anxiety in migraine patients. Methods: Patients with migraine were either selected for acupuncture treatment or no treatment based on the 1:1 propensity score-matched method from the Taiwanese National Health Insurance Research Database between 2000 and 2012 and followed up until the end of 2013. The observed outcome measures were comparison of medical expenditure and incidence of depression/anxiety in the two cohorts. Results: The acupuncture cohort had a lower medical expenditure within 1 year of the intervention than the non-acupuncture cohort (p < 0.001). The acupuncture cohort had a reduced risk of depression (adjusted hazard ratio [HR], 0.61, 95% confidence interval [CI], 0.39–0.95) and anxiety (adjusted HR, 0.51, 95% CI, 0.43–0.59) after adjusting for sex, age, monthly income, urbanization level, occupation category, baseline comorbidities, and medicines used. The Kaplan–Meier analysis revealed that the cumulative incidence of depression and anxiety was significantly lower in the acupuncture cohort than in the non-acupuncture cohort during the 13-year follow-up period (log-rank test, p < 0.001). Conclusions: Acupuncture could reduce medical expenditure and the risk of depression and anxiety during the long-term follow-up period in migraine patients. However, the regulatory effects and mechanisms should be assessed in further clinical research.